PENGARUH METODE CERAMAH DAN DISKUSI TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG PENCEGAHAN MAKROSOMIA DI PUSKESMAS SIABU KABUPATEN MANDAILING NATAL TAHUN 2016 - Rizki Noviyanti (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2020)
Counseling is one of the methods to forestall macrosomia. It play an important role in providing knowledge for pregnant women about macrosomia so that in the future pregnant women can know and act in a certain way to forestall the incidence of macrosomia during pregnancy. The objective of the research was to find out the influence of lecture and discussion methods on pregnant women’s knowledge and attitude toward forestalling macrosomia at Siabu Puskesmas, Mandailing Natal Regency, in 2016. The research used quasi experimental method with pretest-posttest design. 15 respondents were in lecture method group and 15 respondents were in discussion method group. The data were analyzed by using statistic t-independent test at α = 5%. The result of the research showed that there was the influence of lecture and discussion methods on pregnant women’s knowledge of macrosomia. The change in knowledge was bigger in using discussion method at the mean value of 4.33 than lecture method at mea value of 3.58 so that discussion method was more effective in pregnant women’s knowledge of macrosomia that that in lecture method. There was the influence of lecture and discussion methods on pregnant women’s attitude toward macrosomia. The change in attitude was bigger in using discussion method at mean value of 13.20 than that in lecture method at mean value of 8.62 so that discussion method was more effective in pregnant women’s attitude toward macrosomia than that in lecture method. It is recommended that the management of Puskesmas increase people’s participation in pregnant women’s health by providing health counseling about forestalling macrosomia so that they will know the complication caused by macrosomia and how to forestall it. This health education is also an attempt to improve preventive service in health.